Profitability and sustainability of small-scale aquafeed producers in Ghana - Ragasa, Catherine; Osei-Mensah, Yaa Oguabi; Ataa-Asantewa, Martha; Kruijssen, Froukje (SSRN, 2024)
Feed costs constitute about 60–90 percent of total operating costs in aquaculture for many species. To address the growing demand for farmed fish and aquafeeds, large-scale aquafeed producers and exporters have expanded in recent years. However, aquafeeds remain inaccessible and unaffordable to many small-scale producers in many parts of Sub-Saharan Africa, where aquaculture is currently booming. The need for affordable, accessible, and available quality aquafeeds has led to the emergence of innovative on-farm feed production and management practices by fish farmers and small-scale aquafeed production businesses. This study focuses on small-scale aquafeed producers to understand how they contribute to bringing quality aquafeeds to small-scale producers, especially in remote areas, and to evaluate their performance and sustainability. Twelve aquafeed producers and seven of their aquafarmer-clients were interviewed in 2021 and 2022. Of six producers with detailed profit data, five experienced positive profits ranging from 0.34 to 1.86 cedi per kg of feed produced (8–35 percent profit margin). Small-scale producers sell tilapia feed at 3.75–5.33 cedi/kg and catfish feed at 3.25–6.13 cedi/kg, 10–35 percent cheaper than the most popular commercial feed (Raanan), excluding transportation costs. These producers are also fish farmers, allowing for on-farm testing of feed quality and ease of access for their own use. Feed from small-scale producers was more affordable and accessible than feed from Raanan, with reduced transportation costs, discounts, and credit benefits. Increasing costs, inconsistent supply of raw materials, and lack of funds to upgrade their facilities constrain small-scale producers’ expansion. Sustainable supply and stable price of raw materials, training on cost-effective quality feed production, and availability of local grinding and pelletizing machines and parts are the main entry points and strategies to support feed producers and improve the availability of affordable quality aquafeeds.